Resistir é preciso: os referenciais de memória e identidade cultural da Comunidade Quilombola Rufinos no Instagram - Monteiro, Edson Marques Almeida (2024)
The dissertation in question seeks to examine the way in which the Rufinos Quilombola Community, located in the municipality of Pombal-PB, maintains and transmits its traditional knowledge, identity and culture built up over generations, especially in the Instagram environment. It is characterized as exploratory and descriptive, with a qualitative approach and a bibliographic review was carried out covering books, magazine articles, dissertations, theses, official documents and technical reports, to understand the connection between information, memory and cultural identity, as well as the influence of Information and Communication Technologies on the visibility and conservation of the identity of traditional communities. It conceptualizes and characterizes traditional peoples and communities in Brazil, with an emphasis on the Quilombola Communities of Paraíba, specifically the Rufinos Quilombola Community located in the city of Pombal-PB. An empirical study was conducted to map the profiles of the Quilombola Communities of Paraíba on Instagram. The state's Traditional Peoples and Communities were identified and the elements of memory and identity of the Rufinos Quilombola Community were categorized, including traditions, religiosity, celebrations, personalities and other relevant practices. The results showed that Instagram profile posts are a way for people to learn more about the identity and culture of the Rufinos Quilombola Community, making it an excellent tool for social visibility. The contributions that traditional knowledge and practices make to the communities have been observed, both in terms of the survival and resistance of their roots and in terms of financial survival. It can be seen from the posts that the revival of old quilombo traditions is not only a way of rekindling the interest of new generations, but has also become a source of income. The posts made on the @quilomborufinospombal profile are mainly intended to give visibility to the actions and cultural manifestations that constitute and strengthen the quilombo's ancestry. And very little of it is intended to inform about these practices in the context of the community, the history of a particular tradition, etc. But even so, it provides little information about those traditions, customs, etc. We recommend posts with more informative content about customs, gastronomy, ancestral practices and traditions.